2016
DOI: 10.1016/j.bjm.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of carboxylesterase and esterase activity in culturable gut bacterial flora isolated from diamondback moth, Plutella xylostella (Linnaeus), from India and its possible role in indoxacarb degradation

Abstract: Diamondback moth (DBM), Plutella xylostella (Linnaeus), is a notorious pest of brassica crops worldwide and is resistant to all groups of insecticides. The insect system harbors diverse groups of microbiota, which in turn helps in enzymatic degradation of xenobiotic-like insecticides. The present study aimed to determine the diversity of gut microflora in DBM, quantify esterase activity and elucidate their possible role in degradation of indoxacarb. We screened 11 geographic populations of DBM in India and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 26 publications
5
77
0
1
Order By: Relevance
“…We found that the gut bacterial communities of most S. frugiperda samples were dominated by Proteobacteria. This observation is similar to proportions reported in other phytophagous insects, in particular lepidopterans (Belda et al 2011; Xia et al 2013, 2017; Landry et al 2015; Ramya et al 2016; Snyman et al 2016; Strano et al 2017; Chen et al 2018). Only three samples, two adult males from Kitale (Kitale-m2 and Kitale-m3) and one larvae from Ngeria (Ngeria-l2) were dominated by Firmicutes.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the gut bacterial communities of most S. frugiperda samples were dominated by Proteobacteria. This observation is similar to proportions reported in other phytophagous insects, in particular lepidopterans (Belda et al 2011; Xia et al 2013, 2017; Landry et al 2015; Ramya et al 2016; Snyman et al 2016; Strano et al 2017; Chen et al 2018). Only three samples, two adult males from Kitale (Kitale-m2 and Kitale-m3) and one larvae from Ngeria (Ngeria-l2) were dominated by Firmicutes.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, these genera were found to be more abundant in the IR population than in the IS population. All the three genera were previously reported from insect guts [28,35]. The gut-associated enterococci are known to contribute to the fitness of the insect host in several ways, including the prevention of proliferation of the pathogen [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria are mainly associated with the detoxification of organophosphates, although Bacillus spp. can also detoxify oxadiazine insecticides …”
Section: Discussionmentioning
confidence: 99%
“…can also detoxify oxadiazine insecticides. 26,28,60,61 S. symbiotica is one of the most common symbionts of aphids with predominantly mutualistic functions. 11,21,23,62 Some members of genus Serratia are known to be involved in the degradation or detoxification of insecticides and plant toxins.…”
Section: Discussionmentioning
confidence: 99%